Magnetic Resonance Spectroscopy: Role in clinical decision making and accurate diagnosis of the brain lesions - Kalhoro, Aurangzeb; Sattar, Abdul Basit; Abdul Sattar M Hashmi; Rajper, Sanam B (International Journal of Endorsing Health Science Research, 2021)
Background: Magnetic Resonance Spectroscopy (MRS) combined Magnetic Resonance Spectroscopic Imaging (MRSI) can diagnose brain lesions and help manage several diseases. It has the advantage of differentiating neoplastic brain lesions from non-neoplastic brain lesions based on metabolic changes of the brain. The present study focuses on Magnetic Resonance Spectroscopy (MRS) assessment accuracy in the diagnosis of brain lesions. Methodology: A prospective, non-probability, consecutive sampling study was conducted at the Neurospinal & Cancer care institute, Karachi-Pakistan, from June 2017 to September 2020. A total of 161 patients with brain space-occupying lesions shown on MRI brain contrast and associated with clinical symptoms of headache, fits, or limb weakness was included in the study. The single voxel method was used for MRS; after contrast. MRI was used to localize the pathology in the brain, and the voxel was used in the area of heed interest. Results Spectroscopy interpretation showed that 114(70.8%) patients were diagnosed with a brain tumour, 41 (25.46%) had a non-neoplastic entity, and 6 (3.72%) were reported as non-specified. MR Spectroscopy reported non-neoplastic entities in 41 (25.46%) patients by spectroscopy. among them, 39(95.12%) patients had decreased choline, NAA and creatinine peaks, raised lactate peak 16(39.02%), lipid peaks 20(48.78%), while in 4 (9.75%) patients the peaks were absent. Conclusion: This study recommends that MR spectroscopy has a high accuracy for the diagnostic purpose of neoplastic and non-neoplastic, which is 91.33% which can affect the course of the treatment plan and it can help to avoid unnecessary delay in management.